The Teller and the Tale: A Note on Hawthorne's Narrators. - COLACUBCIO, MICHAEL (Nathaniel Hawthorne Review, 2019)
This essay conducts close investigations into the matter of the "tellers" of Nathaniel Hawthorne's tales, beginning with a look at the abortive "Story-Teller" collection with its lost narrative frame, and proceeding through Twice-told Tales and stories of the Old Manse period to the novels. Concentrating especially on some of Hawthorne's most famous unsteady, unstable, or inadequate narrators--like those in "The Birth-mark," "The Artist of the Beautiful," "Rappaccini's Daughter," and "Main-street"--the author poses the questions: whom or what should one trust, when reading Hawthorne's works, and where is the author in all this?.